Recent advances in surface decoration of nanoparticles in drug delivery - Ly, Phuong-Dung; Ly, Ky-Nhu; Phan, Hoang-Long; Nguyen, Huong H. T.; Duong, Van-An; Nguyen, Hien V. (Frontiers in Nanotechnology, 2024)
for enhanced drug bioavailability and targeted delivery. Specifically, these systems can enhance the solubility of poorly water-soluble drugs, protect therapeutic agents from degradation, prolong circulation time in the body, control drug release, and facilitate the precise targeting of drugs to specific tissues or cells. However, once administered into the body, nanoparticles often encounter significant challenges that can affect their efficacy and safety, such as issues with stability, biocompatibility, and targeting. The surface properties of nanoparticles are one of the most important features as they can greatly influence the interactions between nanoparticles themselves and between nanoparticles and biological targets. Key surface characteristics, such as charge, hydrophobicity, and the presence of functional groups, determine how nanoparticles behave in biological environments, thereby influencing their stability, cellular uptake, and ability to avoid immune clearance. Modification of the nanoparticle surface has been shown to be an effective approach to modulate the physicochemical and biological properties of nanoparticles, achieving desired therapeutic efficacy in vivo. This review aims to summarize recent advances in surface decoration of nanoparticles, with an emphasis on improved colloidal and biological stability, reduced toxicity, and enhanced drug targeting. The challenges and future perspectives of nanoparticle surface modification approaches are also discussed.